Methods for the directed evolution of proteins - Packer, Michael S.; Liu, David R. (Nature reviews. Genetics, 2015)
Key Points Directed evolution is a cyclic process that alternates between gene diversification and screening for or selection of functional gene variants. Library size limitations can be overcome by focusing library diversity on residues implicated by molecular structures, computational models or phylogenetic data. In cases in which there is limited information, random mutagenesis can be used to interrogate the uncertain determinants of protein function. Recombination methodologies access new combinations of functional variation and can shuffle disparate genetic elements to yield new chimeric proteins. Low-throughput screens can directly measure individual phenotypes and thus accurately isolate desired subpopulations. Screen throughput can be increased using indirect visible reporters that are strongly coupled to the desired phenotypes. Selections isolate functional variants through selective replication schemes or physical segregation. Selections operate simultaneously on entire populations and thus offer unparalleled throughput. Directed evolution uses laboratory-based evolution to enhance the properties of biomolecules, primarily to generate proteins with optimized or novel activities. This Review discusses the diverse range of technologies for the directed evolution of proteins, particularly methods for generating diversity in the gene library and approaches for screening and selecting for variants with desired properties. The relative strengths and limitations of these approaches are highlighted to guide readers to appropriate strategies. Directed evolution has proved to be an effective strategy for improving or altering the activity of biomolecules for industrial, research and therapeutic applications. The evolution of proteins in the laboratory requires methods for generating genetic diversity and for identifying protein variants with desired properties. This Review describes some of the tools used to diversify genes, as well as informative examples of screening and selection methods that identify or isolate evolved proteins. We highlight recent cases in which directed evolution generated enzymatic activities and substrate specificities not known to exist in nature.